Safety and efficacy of C1-inhibitor in traumatic brain injury (CIAO@TBI): study protocol for a randomized, placebo-controlled, multi-center trial - Inge A. M. van Erp (BMC, 2021)
Abstract Background Traumatic brain injury (TBI) is a major cause of death and disability across all ages. After the primary impact, the pathophysiologic process of secondary brain injury consists of a neuroinflammation response that critically leads to irreversible brain damage in the first days after the trauma. A key catalyst in this inflammatory process is the complement system. Inhibiting the complement system could therefore be a therapeutic target in TBI. Objective To study the safety and efficacy of C1-inhibitor (C1-INH) compared to placebo in patients with TBI. By temporarily blocking the complement system, we hypothesize a decrease in the posttraumatic neuroinflammatory response resulting in a less unfavorable clinical outcome for TBI patients. Methods CIAO@TBI is a multicenter, randomized, blinded, phase II placebo-controlled trial. Adult TBI patients with GCS < 13 requiring intracranial pressure (ICP) monitoring will be randomized, using block randomization, within 12 h after trauma to one dose 6000 IU C1-INH or placebo. A total of 106 patients will be included, and follow-up will occur up to 12 months. The primary endpoints are (1) Therapy Intensity Level (TIL) Scale, (2) Glasgow Outcome Scale-Extended (GOSE) at 6 months, and (3) complication rate during hospitalization. Outcomes will be determined by a trial nurse blinded for the treatment allocation. Analyses will be conducted in an intention-to-treat analysis. Discussion We expect that C1-INH administration will be safe and potentially effective to improve clinical outcomes by reducing neuroinflammation in TBI patients. Trial registration ClinicalTrials.gov NCT04489160. Registered on 27 July 2020. EudraCT 2020-000140-58